Structural, optical and thermal properties of nickel doped bismuth borate glasses - Thakur, Seema; Thakur, Vanita; Kaur, Anumeet; Singh, Lakhwant (Journal of non-crystalline solids, 2019)
Nickel doped Bismuth Borate glasses with composition (70B2O3-(30-x)Bi2O3-xNiO) where x = 0,0.5,1.0,1.5,2.0 (wt%) have been synthesized by conventional melt quenching technique. X-Ray Diffractograms have confirmed the amorphous nature of the prepared glasses. The calculated physical parameters such as density, molar volume, average boron‑boron separation, ion concentration and inter ionic distance provided the information about the structural stability of glass samples. DTA and OPD confirmed the decrease in glass transition temperature (Tg) with increase in Ni content. The FTIR and Raman studies clearly revealed that the glass network mainly comprises of [BiO3], [BiO6], [BO3] and [BO4] units. It is also observed that the introduction of dopant (Ni) and modifier (Bi) leads to the conversion of [BO3] trigonal units into the [BO4] tetragonal units due to the increase in non-bridging oxygen atoms which results in the increase of degree of disorder in the glass network. The optical absorption measurements (UV) carried out for well polished glass samples show a decrease in optical band gap with the increase in Ni doping. This observation was further supported by the urbach energy calculations and metallization criterion of the prepared glass samples. The electronegativity and electronic polarizability values revealed the ionic character of glass samples.